2008
DOI: 10.1021/bm800808q
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Block Copolymers of Poly(ethylene glycol) and Polyphosphoester: Thermo-Induced Self-Assembly, Biocompatibility, and Hydrolytic Degradation

Abstract: Novel thermoresponsive block copolymers of poly(ethylene glycol) and polyphosphoester were synthesized, and the thermo-induced self-assembly, biocompatibility, and hydrolytic degradation behavior were studied. The block copolymers with various molecular weights and compositions were synthesized through ring-opening polymerization of 2-ethoxy-2-oxo-1,3,2-dioxaphospholane (EEP) and 2-isopropoxy-2-oxo-1,3,2-dioxaphospholane (PEP) using poly(ethylene glycol) monomethyl ether (mPEG) as the initiator and stannous oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 49 publications
(82 reference statements)
1
109
0
3
Order By: Relevance
“…1, C and D) (17, 18). Specifically, we decorated the ends of P407 with an aliphatic polyphosphoester (PPE), one of a class of generally biocompatible and biodegradable polymers (17, 19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, C and D) (17, 18). Specifically, we decorated the ends of P407 with an aliphatic polyphosphoester (PPE), one of a class of generally biocompatible and biodegradable polymers (17, 19).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we decorated the ends of P407 with an aliphatic polyphosphoester (PPE), one of a class of generally biocompatible and biodegradable polymers (17, 19). Block copolymers of PPE with aliphatic side chains demonstrate reverse thermal gelation (17, 20), likely owing to the breaking of hydrogen bonding with ambient water molecules at elevated temperature (20). Their side chains (such as methyl, ethyl, and isopropyl) can be changed easily to tune the hydrophobicity and temperature responsiveness (21).…”
Section: Resultsmentioning
confidence: 99%
“…This copolymer formed micelles above its LCST but also showed pH responsive degradation giving another option for drug release [108]. Polymers with similar properties were produced by Hruby et al based on poly oxazolines [109] and Wang et al based on PEO [110]. The thermoresponsive properties of terpolymers of PEGMA-b-(DMAEMA-co-MMA) were shown to have an interesting pH and temperature sensitivity [111].…”
Section: Micellesmentioning
confidence: 94%
“…It was speculated that the serum-enhanced transfection activity was related to the phosphoester modification. It has been reported that the polyphosphoester shows to some extent serum-resistant ability [36].…”
Section: Resultsmentioning
confidence: 99%